2020
DOI: 10.2131/jts.45.599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serial cervical or tail blood sampling on toxicity and toxicokinetic evaluation in rats

Abstract: To assess the influences of blood sampling volumes or sites on toxicological and toxicokinetic (TK) evaluations, 4-week duration animal studies and a single-dose TK study of imipramine were conducted. In the toxicological evaluation, six-week-old Sprague-Dawley rats were divided into no blood and blood sampling groups. Fifty microliters (microsampling) or 100 μL (larger sampling) of blood/time point was collected from the jugular vein (50 μL of data was reported previously as Yokoyama et al., 2020) or the tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…When microsampling is performed from the jugular vein, effects on the site of blood collection are sometimes inevitable. In fact, hemorrhage lesions were observed subcutaneously in the neck of all rats and in the thoracic cavity of a female, which were related to the blood sampling site (Hattori et al, 2020). The cause of the hematological parameter changes was assumed by the authors to be caused by further blood loss at the local sampling site in addition to the volume of actual blood collected from the jugular vein since no degenerative changes in the hematopoietic organs were observed in the histopathological examination.…”
Section: Influence Of Microsampling On the Toxicity Parameters In Rat...mentioning
confidence: 99%
See 3 more Smart Citations
“…When microsampling is performed from the jugular vein, effects on the site of blood collection are sometimes inevitable. In fact, hemorrhage lesions were observed subcutaneously in the neck of all rats and in the thoracic cavity of a female, which were related to the blood sampling site (Hattori et al, 2020). The cause of the hematological parameter changes was assumed by the authors to be caused by further blood loss at the local sampling site in addition to the volume of actual blood collected from the jugular vein since no degenerative changes in the hematopoietic organs were observed in the histopathological examination.…”
Section: Influence Of Microsampling On the Toxicity Parameters In Rat...mentioning
confidence: 99%
“…Similarly, assuming a typical 4‐week general toxicity study (Exp 1) in rats, serial blood sampling was performed on Days 1 to 2 and 27 to 28 from the jugular vein (Hattori et al, 2020). Blood sampling volume was 6 or 7 × 100 μl.…”
Section: Influence Of Microsampling On the Toxicity Parameters In Rat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our team has performed several evaluation studies for the effects of microsampling on toxicological parameters or TK parameters using the rat model. It has been demonstrated that microsampling from the jugular vein and tail vein shows low concern for preventing evaluation in typical toxicity studies, that there is no marked influence on toxicity parameters between blood sampling sites; this is a practicable technique in a wide range of study organizations (Yokoyama et al, 2020;Hattori et al, 2020). However, one challenge is that the data of our previous reports stated above were obtained from animals maintaining normal homeostasis, and there is a limited information for estimating the microsampling effect on toxicity parameters in animals exhibiting adverse reactions due to drug exposure.…”
Section: Introductionmentioning
confidence: 99%